Vascular Pedicle and Microchannels: Simple Methods Toward Effective In Vivo Vascularization of 3D Scaffolds. Issue 24 (12th November 2019) - Rnjak‐Kovacina, Jelena; Gerrand, Yi‐wen; Wray, Lindsay S.; Tan, Beryl; Joukhdar, Habib; Kaplan, David L.; Morrison, Wayne A.; Mitchell, Geraldine M.
Abstract: Poor vascularization remains a key limiting factor in translating advances in tissue engineering to clinical applications. Vascular pedicles (large arteries and veins) isolated in plastic chambers are known to sprout an extensive capillary network. This study examined the effect vascular pedicles and scaffold architecture have on vascularization and tissue integration of implanted silk scaffolds. Porous silk scaffolds with or without microchannels are manufactured to support implantation of a central vascular pedicle, without a chamber, implanted in the groin of Sprague Dawley rats, and assessed morphologically and morphometrically at 2 and 6 weeks. At both time points, blood vessels, connective tissue, and an inflammatory response infiltrate all scaffold pores externally, and centrally when a vascular pedicle is implanted. At week 2, vascular pedicles significantly increase the degree of scaffold tissue infiltration, and both the pedicle and the scaffold microchannels significantly increase vascular volume and vascular density. Interestingly, microchannels contribute to increased scaffold vascularity without affecting overall tissue infiltration, suggesting a direct effect of biomaterial architecture on vascularization. The inclusion of pedicles and microchannels are simple and effective proangiogenic techniques for engineering thick tissue constructs as both increase the speed of construct vascularization in the early weeks post in vivo implantation. Abstract : In an in vivo study, the presence of vertical microchannels within a thick porous silk scaffold, and the placement of the femoral artery and vein through the scaffold centrally, both resulted in significant increases in scaffold blood vessel ingrowth by 2 weeks as measured by the percent vascular volume, and density mm −2 of blood vessels within the scaffold.